Answered

Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Join our Q&A platform to get precise answers from experts in diverse fields and enhance your understanding. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

Solve the system of equations using the elimination method
2y - 3y = -9
-x + 3y = 6
(-3,3)
(1,3)
(3,3)
(-3,1)

right answer gets brainliest


Solve The System Of Equations Using The Elimination Method 2y 3y 9 X 3y 6 33 13 33 31 Right Answer Gets Brainliest class=

Sagot :

9514 1404 393

Answer:

  (d)  (-3, 1)

Step-by-step explanation:

We assume a typo in the problem statement, and that the equations are supposed to be ...

  [tex]2x -3y = -9\\-x +3y = 6[/tex]

Adding the two equations gives ...

  x = -3

Substituting for x in the second equation gives ...

  3 +3y = 6

  1 + y = 2 . . . . divide by 3

  y = 1 . . . . . . . subtract 1

The solution is (x, y) = (-3, 1).

View image sqdancefan